About Youth of Kazakhstan (Journal of Philosophy Culture and Political Science, 2018)
The modern youth of Kazakhstan is the subject of history, Kazakhstan society has discovered it for itself as a social value of a special kind. The current youth is an exceptional and important factor for change, a carrier of new ideas. In this connection, a modern state youth policy that meets the needs of the 21st century is necessary.